Lung ultrasound score before and after extubation for predicting weaning outcome - Yadav, Manoj Kumar; Pal, Anusmriti; Pant, Chiranjibi; Shrestha, Bishow Kumar (Journal of Chitwan Medical College, 2019)
Background: Lung ultrasound (LUS) is an emerging, essential, safe and easily repeatable bedside tool being used for the management of critically ill patients in ICUs. Weaning off the ventilator and decide to extubate require right decision and appropriate timing to avoid extubation failure. The study aimed to perform LUS in planned extubation patients who passed SBT, for the assessment of lungs, before and after extubation. Methods: A single-centre, observational study at medical ICU of a tertiary level hospital in Nepal was conducted on invasive mechanically ventilated patients. LUS was performed before extubation on those who were planned to extubate and repeat scan done after 24 hours of extubation. LUS scores were calculated at both times. p-value 0.05 was considered statistically significant. Results: Twenty-eight patients were included after passing spontaneous breathing trial (SBT), one patient had extubation failure. Mean LUS score before and after extubation came to be 16.15 ± 7.00 and 13.15 ± 4.59 respectively with high degree of correlation (Pearson’s r = 0.896, P <0.001). The mean difference in LUS scores before and after extubation was significant (Mean difference: 3.00 ± 3.54, t = 4.402, p < 0.001). Conclusions: Lung ultrasound is very useful additive tool in predicting extubation failure easily and timely. Its use after extubation also helps in early prediction of post-extubation failure by assessing aeration changes and other lung pathology.